SAT0178 Clinical Responses of Sarilumab Based on Rheumatoid Factor and Anti–Cyclic Citrullinated Peptide Antibody Status in Patients with Rheumatoid Arthritis. (15th July 2016) - Emery, P.; van Hoogstraten, H.; Mangan, E.K.; van Adelsberg, J.; Fan, C.; Kivitz, A.; Pinheiro, G.da R.C.; Huizinga, T.
Abstract : Background: Sarilumab is a human investigational anti–IL-6 receptor mAb that has been studied in 2 randomized, double-blind, placebo-controlled, multicenter, phase 3 studies in patients with RA. Subcutaneous (SC) sarilumab q2w + MTX demonstrated efficacy in patients with inadequate response to MTX in the MOBILITY study (NCT01061736 ). 1 Sarilumab SC q2w + conventional synthetic DMARDs demonstrated efficacy in patients who were inadequate responders to or intolerant of TNFi in the TARGET study (NCT01709578 ). 2 The most common TEAEs in both studies were infections, neutropenia, injection site reactions, and increased transaminases. Objectives: Negative autoantibody status has been associated with attenuated clinical response to biologic disease-modifying agents in RA. 3, 4 This study assessed the clinical efficacy of sarilumab in subgroups of patients based on rheumatoid factor (RF) and anti-CCP antibody status in MOBILITY and TARGET. Methods: Incidence of ACR20/50/70 response at wk 24, mean change from baseline in HAQ-DI at wk 12 (TARGET) or 16 (MOBILITY), and DAS28-CRP at wk 24 were evaluated by RF and CCP status. Results: The majority of MOBILITY (78%) and TARGET (70%) patients were RF+/CCP+. Treatment-by-subgroup interaction ( P <0.05) was observed for ACR20 response (CCP status in MOBILITY; RF and CCP in TARGET) and HAQ-DI (RF and CCP status in MOBILITY; RF in TARGET). Clinical and functional responses in RF/CCP single- and double-positive patients were generally similar to overall study results (Table ). However, certain clinical measures, including HAQ-DI, showed a trend toward smaller effect sizes, particularly in double-negative patients, that was somewhat more pronounced with sarilumab 150 mg q2w (Table ), though sample sizes were small. Comparable findings were observed for DAS28-CRP: mean change from baseline for placebo + MTX, sarilumab 150 mg q2w + MTX, and sarilumab 200 mg q2w + MTX was -1.56 (n=191), -2.75 (n=257), and -3.09 (n=246), respectively, for RF+/CCP+ patients and -1.97 (n=22), -2.10 (n=13), and -2.51 (n=20), respectively, for RF-/CCP- patients in MOBILITY. TARGET results were similar. Trends toward lower clinical and functional responses with RF or CCP negative autoantibody were not observed in radiographic measurements of structural progression; change from baseline in mTSS appeared to be similar regardless of autoantibody status (data on file). Conclusions: Overall, within MOBILITY and TARGET, clinical responses with sarilumab were generally consistent among patients who were RF+ and/or CCP+. Regardless of autoantibody status, there was a more robust response with regard to clinical signs and symptoms with sarilumab 200 mg q2w. References: Genovese et al. Arthritis Rheumatol. 2015;67:1424–1437 Fleischmann et al. Presented at: ACR; November 7–11, 2015; San Francisco, CA Alten et al. Presented at: ACR; November 7–11, 2015; San Francisco, CA Chatzidionysiou et al. Ann Rheum Dis. 2011;70:1575–1580 Acknowledgement: This study was sponsored by Sanofi and Regeneron Pharmaceuticals, Inc. Editorial assistance was provided by Rebecca Slager, PhD, MS, MedThink SciCom, and funded by Sanofi and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: P. Emery Consultant for: AbbVie, Bristol-Myers Squibb, Lilly, MSD, Novartis, Pfizer, Roche, Samsung, Sandoz, and UCB, H. van Hoogstraten Shareholder of: Sanofi, Employee of: Sanofi, E. Mangan Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, J. van Adelsberg Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, C. Fan Shareholder of: Sanofi, Employee of: Sanofi, A. Kivitz Consultant for: Sanofi, Pfizer, Roche, and UCB, G. da R.C. Pinheiro Consultant for: AbbVie, AstraZeneca, GlaxoSmithKline, Hospira, Janssen, Pfizer, Roche, RuiYi, and Sanofi, T. Huizinga Consultant for: Sanofi